Communication barriers and deaf learner misbehaviour in a South African special needs school - Ratidzai Shoko (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2024)
Mainstream schools often encounter problems with learner behaviour which disrupt effective teaching and learning. Inclusive special schools with learners with disabilities, including learners who are deaf, are not spared such problems. This is so especially when they face the challenges of communication barriers. This paper focuses on the influence of communication barriers on misbehaviour by learners who are deaf. The research was a qualitative case study conducted in Gauteng province of South Africa at an inclusive special needs school with learners with disabilities. It aimed to establish the effectiveness of interventions for managing behaviour among the learners. The study found that effective communication plays a vital role in the positive management of the behaviour of deaf learners. It recommends that the learners who are deaf be provided access to language and specialized communication support and language resources such as oral interpreting, sign language, and hearing aids.